The WANDA Reflective Method as a Tool for Improving Teachers’ Well-being - Poche Kargerová, Jana; Göbelová, Taťána; Šimlová, Žaneta; Seberová, Alena (Revija za elementarno izobraževanje, 2025)
This qualitative research study focuses on teachers’ well-being in the context of the WANDA reflective method. The aim was to explore teachers’ subjective perceptions of the benefits of WANDA on their well-being. Data were collected through a qualitative written interview technique. The research sample consisted of sixteen primary and pre-primary teachers who had completed the WANDA method. Content analysis of the data was conducted using thematic analysis based on the PERMA model. The results showed that WANDA contributes to teachers’ well-being in the areas of Relationship, Meaning, Positive Emotions, and Engagement. The Accomplishments category was the least represented.
Keywords: WANDA, well-being, teachers’ well-being, PERMA.